2015
DOI: 10.1016/j.cell.2015.08.062
|View full text |Cite|
|
Sign up to set email alerts
|

A Hierarchical Multi-oscillator Network Orchestrates the Arabidopsis Circadian System

Abstract: Short- and long-distance circadian communication is essential for integration of temporal information. However, a major challenge in plant biology is to decipher how individual clocks are interconnected to sustain rhythms in the whole plant. Here we show that the shoot apex is composed of an ensemble of coupled clocks that influence rhythms in roots. Live-imaging of single cells, desynchronization of dispersed protoplasts, and mathematical analysis using barycentric coordinates for high-dimensional space show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
173
0
16

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(216 citation statements)
references
References 54 publications
(69 reference statements)
11
173
0
16
Order By: Relevance
“…As discussed in this article, recent work demonstrated that the expression patterns of the clock genes show tissue-specific variations in Arabidopsis, and that the clock in each specific tissue differently affects each specific output, as it was shown that the functional vascular clock is essential for controlling photoperiodic flowering (Endo et al, 2014;Shimizu et al, 2015). As was also shown recently, the plant clock in each cell can synchronize within and across the tissues (Wenden et al, 2012;Takahashi et al, 2015;Muranaka and Oyama, 2016), although they can independently sustain circadian rhythmicity in clock gene transcription. Similar to the synchronization of the clock-regulated genes observed, do the phloem companion cells that express FT also communicate with each other to coordinate the timing of expression of FT?…”
Section: Future Perspectivesmentioning
confidence: 84%
“…As discussed in this article, recent work demonstrated that the expression patterns of the clock genes show tissue-specific variations in Arabidopsis, and that the clock in each specific tissue differently affects each specific output, as it was shown that the functional vascular clock is essential for controlling photoperiodic flowering (Endo et al, 2014;Shimizu et al, 2015). As was also shown recently, the plant clock in each cell can synchronize within and across the tissues (Wenden et al, 2012;Takahashi et al, 2015;Muranaka and Oyama, 2016), although they can independently sustain circadian rhythmicity in clock gene transcription. Similar to the synchronization of the clock-regulated genes observed, do the phloem companion cells that express FT also communicate with each other to coordinate the timing of expression of FT?…”
Section: Future Perspectivesmentioning
confidence: 84%
“…6). Recent work shows that the shoot apex sends an unidentified signal to roots that maintains circadian synchrony within roots (Takahashi et al ., 2015). While lack of this signal may account for the progressive loss of rhythmicity in decapitated roots, our data show that it can be overcome by direct exposure of roots to LD cycles even at intensities as low as 0.15 μmol m −2  s −1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Takahashi et al . (2015) showed that the clocks in shoot apex cells are coupled by intercellular communication and can send a signal to roots that maintains circadian synchrony within roots, such that root rhythms damp rapidly after excision of the apex; they also confirmed the period difference between shoots and roots.…”
Section: Introductionmentioning
confidence: 90%
“…Plant cells act as self-sustained oscillators, with their own circadian clocks that regulate interactions with surrounding cells. Phase waves in leaves and roots (Fukuda et al, 2007;Wenden et al, 2012;Ukai et al, 2012;Fukuda et al, 2012), differences in inherent periods between tissues (Endo et al, 2014;Takahashi et al, 2015;Bordage et al, 2016), and spatiotemporal analytical data (Fukuda et al, 2007;James et al, 2008;Wenden et al, 2012;Fukuda et al, 2013) suggest that the cellular oscillator network involves nonlinear phenomena. It was also reported that growth and developmental processes in roots exhibit marked spatiotemporal patterns, such as striped waves resulting from strong phase resetting in the elongation-differentiation (ED) region of the root tip.…”
Section: Introductionmentioning
confidence: 99%